2015
DOI: 10.1590/1516-635xspecialissuenutrition-poultryfeedingadditives099-104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Inclusion of a Probiotic, a Prebiotic or their Combinations on the Growth Performance of Broiler Chickens

Abstract: A total of 350-one-day old chicks were placed in 70 cages, with 14 cages per treatment. The following five treatment diets were fed for 14 days: T1 = non-supplemented, control diet (CONT); T2 = diet with antimicrobial growth promoter (AGP); T3 = diet with a probiotic (PROB); T4 = diet with a prebiotic(PREB), and T5 = diet with the probiotic and the prebiotic (SYM). The growth experiment was carried out from 1 to 14 days of age. Feed and water were provided ad libitum and birds were maintained at 24-h light sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…[45] observed a similar effect of improved FCE after administration of synbiotics in broiler chicken diets. In contrast, Murshed and Abudabos [46] reported poorer FCE in chickens fed diets with a synbiotic consisting of MOS, beta-glucans, and a highly active strain of Bacillus subtilis (DM17299). Moreover, high doses of dietary probiotic tended to increase FCE in later stages of broiler rearing [47].…”
Section: Discussionmentioning
confidence: 99%
“…[45] observed a similar effect of improved FCE after administration of synbiotics in broiler chicken diets. In contrast, Murshed and Abudabos [46] reported poorer FCE in chickens fed diets with a synbiotic consisting of MOS, beta-glucans, and a highly active strain of Bacillus subtilis (DM17299). Moreover, high doses of dietary probiotic tended to increase FCE in later stages of broiler rearing [47].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of probiotics on feed consumption can also vary depending on the strain used. The feeding of broiler chickens with probiotics resulted in a significant reduction in feed conversion ratio (FCR) and feed consumption per kg of bird weight gain compared to birds not fed probiotics (16). Meanwhile no effect of probiotic addition to feed (Lb.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics make effective changes in the intestinal microbial population and maintain its natural microbial flora by stimulating the growth and proliferation of useful bacteria. Improvement in growth performance and feed efficiency of broiler chickens confirmed by feeding probiotics supplements (Cavazzoni et al 1998;Zulkifli et al 2000;Mountzouris et al 2007;Samli et al 2007;Murshed and Abudabos 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies indicated that addition of organic acid to the DW helps to reduce the level of pathogens in the water and the crop or proventriculus, to regulate gut microflora, to increase the digestion of feed and to improve growth performance (Khan and Iqbal 2016). The use of probiotic and acidifier together are more beneficial than the use of those alone (Rodr ıguez-Lecompte et al 2012; Agboola et al 2015;Murshed and Abudabos 2015). The present study was carried out to evaluate the effect of vinegar (as a native and inexpensive acidifier with easy access) combined with probiotic on broiler chickens performance, carcase yields, immunological responses and the small intestinal morphology.…”
Section: Introductionmentioning
confidence: 99%